An experimental assessment of the efficacy of falconry to mitigate human-wildlife conflict: Egyptian Geese Alopochen aegyptiaca at golf courses - Atkins, Alexander (Percy FitzPatrick Institute of African Ornithology, 2015)
Includes bibliographical references